Egg arrangement in avian clutches covaries with the rejection of foreign eggs - Polačiková, Lenka; Takasu, Fugo; Stokke, Bård G; Moksnes, Arne; Røskaft, Eivin; Cassey, Phillip; Hauber, Mark E; Grim, Tomáš (Animal cognition, 2013)
In birds, the colour, maculation, shape, and size of their eggs play critical roles in discrimination of foreign eggs in the clutch. So far, however, no study has examined the role of egg arrangement within a clutch on host rejection responses. We predicted that individual females which maintain consistent egg arrangements within their clutch would be better able to detect and reject foreign eggs than females without a consistent egg arrangement (i.e. whose eggs change positions more often across incubation). We tested this "egg arrangement hypothesis" in blackbirds (Turdus merula) and song thrush (T. philomelos). Both species are suitable candidates for research on egg rejection, because they show high inter-individual variation and individual repeatability in egg rejection responses. As predicted, using our custom-defined metrics of egg arrangement, rejecter females' clutches showed significantly more consistent patterns in egg arrangement than acceptor females' clutches. Only parameters related to blunt pole showed consistent differences between rejecters and acceptors. This finding makes biological sense because it is already known that song thrush use blunt pole cues to reject foreign eggs. We propose that a disturbance of the original egg arrangement pattern by the laying parasite may alert host females that maintain a consistent egg arrangement to the risk of having been parasitized. Once alerted, these hosts may shift their discrimination thresholds to be more restrictive so as to reject a foreign egg with higher probability. Future studies will benefit from experimentally testing whether these two and other parasitized rejecter host species may rely on the use of consistent egg arrangements as a component of their anti-parasitic defence mechanisms.
Keywords: Nesting Behavior; rozpoznávání obrazu; Clutch Size; Eggs; ženské pohlaví; zvířata; Birds; ptáci; velikost snůšky; vejce; hnízdění; Female; rozpoznávání (psychologie); Pattern Recognition, Visual; Recognition, Psychology; Animals